DISTANCE LEARNING SYSTEM: ITS ADVANTAGES, LIMITATIONS AND IMPLEMENTATION IN MEDICAL EDUCATION (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Distance learning has become a fundamental component of modern education, especially after global digital transformation and pandemics. Studies show that over 70% of universities worldwide adopted online learning systems during recent years. In medical education, the integration of distance learning provides flexibility and accessibility, but also raises concerns regarding clinical competence. This article analyzes advantages, limitations, and implementation strategies supported by statistical and scientific perspectives